2005
DOI: 10.1128/jvi.79.17.11095-11104.2005
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody AP33 Defines a Broadly Neutralizing Epitope on the Hepatitis C Virus E2 Envelope Glycoprotein

Abstract: Hepatitis C virus (HCV) remains a significant threat to the general health of the world's population, and there is a pressing need for the development of new treatments and preventative vaccines. Here, we describe the generation of retrovirus-based pseudoparticles (HCVpp) incorporating a panel of full-length E1E2 clones representative of the major genotypes 1 through 6, and their application to assess the reactivity and neutralizing capability of antisera and monoclonal antibodies raised against portions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
305
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(313 citation statements)
references
References 72 publications
(102 reference statements)
7
305
0
1
Order By: Relevance
“…Therefore, we isolated and tested a large number of E1E2 clones for their ability to confer infectivity to HCVpp. A total of 37 full-length E1E2 clones representative of genotypes 1 through to 6 were shown to be functional in the HCVpp entry assay (not shown), some of which have been reported previously (29,39). Amino acid sequence alignments, corresponding to positions 412 to 424, 474 to 495, and 520 to 550 were generated for these E1E2 clones, together with E1E2 sequences of known infectious reference clones available through the Los Alamos HCV Sequence Database (http://hcv.lanl.gov/content/hcv-db/index).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we isolated and tested a large number of E1E2 clones for their ability to confer infectivity to HCVpp. A total of 37 full-length E1E2 clones representative of genotypes 1 through to 6 were shown to be functional in the HCVpp entry assay (not shown), some of which have been reported previously (29,39). Amino acid sequence alignments, corresponding to positions 412 to 424, 474 to 495, and 520 to 550 were generated for these E1E2 clones, together with E1E2 sequences of known infectious reference clones available through the Los Alamos HCV Sequence Database (http://hcv.lanl.gov/content/hcv-db/index).…”
Section: Resultsmentioning
confidence: 99%
“…(12). Similarly, W420A mutation abolished both MAb AP33 (itself a broadly neutralizing antibody [39]) and CD81 binding, indicating overlap between the CD81 binding site and the AP33 epitope. Finally, mutations at L413, N415, and G418 also reduced the binding of MAb AP33, and we have recently shown that these, together with W420, are probable contact residues (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, they can be used in S2 containment facilities, an undeniable advantage in particular for antiviral screens [156]. Secondly, they are flexible tools able to incorporate a collection of patient-derived glycoproteins [157,158] (a detailed protocol for the generation of such HCVpp can be found in reference [159]), a feature particularly useful to characterize cross-neutralizing antibodies [158,160]. Thirdly, HCVpp proved to be a relevant model to study the mechanisms and steps of virus entry, with for instance the description of HCV internalization [146,147], of the cellular signalling cascades activated upon virus entry [141], or to reveal new receptors for the virus [116,119].…”
Section: Retroviral Hcv Pseudoparticles (Hcvpp): a Specific Entry Systemmentioning
confidence: 99%
“…Proteins were electrotransferred to a polyvinylidene difluoride membrane (Bio-Rad, Hercules, CA) and probed with a mouse monoclonal antibody (mAb) to HCV core (Anogen, Mississauga, Canada); E2 (clone Ap33) (Owsianka et al, 2005); or rabbit polyclonal antibodies to caspase-3 (Cell Signaling Technology, Beverly, MA), GRP78 or CHOP/ GADD153 (Santa Cruz Biotechnology, San Diego, CA), followed by incubation with a horseradish peroxidase (HRP)-conjugated goat anti-mouse IgG or anti-rabbit IgG (Southern Biotechnology Associates, Birmingham, AL), and ECL detection reagents (Amersham Pharmacia, Buckinghamshire, England). Expression levels were evaluated by quantification of the relative density of each band normalized to β-actin.…”
Section: Western Blotting and Immunohistochemistrymentioning
confidence: 99%